Disaster-related deaths with alcohol-related diseases after the Fukushima Daiichi nuclear power plant accident: case series - Kitazawa, Kemmei; Sawano, Toyoaki; Uchi, Yuna; Kawashima, Moe; Yoshimura, Hiroki; Murakami, Michio; Nonaka, Saori; Saito, Hiroaki; Sakakibara, Mamoru; Yagiuchi, Kazuko; Otsuki, Mako; Ozaki, Akihiko; et al. (Frontiers in Public Health, 2024)
Introduction The health of patients with mental disorders, such as alcohol-related diseases, often deteriorates after disasters. However, the causes of death among those with alcohol-related diseases during and after radiation disasters remain unclear. Methods To minimize and prevent alcohol-related deaths in future radiation disasters, we analyzed and summarized six cases of alcohol-related deaths in Minamisoma City, a municipality near the Fukushima Daiichi nuclear power plant. Results Patients were generally treated for alcohol-related diseases. In one case, the patient was forced to evacuate because of hospital closure, and his condition worsened as he was repeatedly admitted and discharged from the hospital. In another case, the patient’s depression worsened after he returned home because of increased medication and drinking for insomnia and loss of appetite. Discussion The overall findings revealed that, in many cases, evacuation caused diseases to deteriorate in the chronic phase, which eventually resulted in death sometime after the disaster. To mitigate loss of life, alcohol-related diseases must be addressed during the chronic phases of future large-scale disasters, including nuclear disasters.